Selective Fe(ii)-fluorescence sensor with validated two-consecutive working range using N,S,I-GQDs associated with garlic extract as an auxiliary green chelating agent - Nipaporn Pimsin; Chayanee Keawprom; Yonrapach Areerob; Nunticha Limchoowong; Phitchan Sricharoen; Prawit Nuengmatcha; Won-Chun Oh; Saksit Chanthai (My University, 2022)
The goal of this work was to use the pyrolysis process to synthesize graphene quantum dots doped with garlic extract (as N,S-GQDs) and simultaneously co-doped with iodine (as I-GQDs). XPS, HR-TEM, FE-SEM/EDX, FT-IR, fluorescence, and UV-visible absorption spectroscopy were used to characterize the N,S,I-GQDs and analyze their morphological images. The quantum yield of N,S,I-GQDs was found to be 45%, greater than that of undoped GQDs (31%). When stimulated at 363 nm, the N,S,I-GQDs display a strong fluorescence intensity at a maximum wavelength of 454 nm. Using N,S,I-GQDs as a fluorescence quenching sensor for screening tests with various metal ions, it was discovered that they are extremely selective towards Fe2+ over Fe3+ and other ions. Thus, solution pH, concentration of N,S,I-GQDs, quantity of garlic extract, EDTA and AgNO3 concentration as masking agents, reaction duration under ultrasonic aid, and tolerable limit of Fe3+ presence in the target analyte were all optimized for Fe2+ detection. A highly sensitive detection of Fe2+ was obtained using a linear curve with y = 141.34x + 5.5855, R 2 = 0.9961, LOD = 0.11 mg L-1, and LOQ = 0.35 mg L-1. The method precision, given as RSDs, was determined to be satisfactory at 1.04% for intra-day analysis and 3.22% for inter-day analysis, respectively. As a result, the selective determination of trace amounts of Fe2+ in real water samples using such labile multi-element doped GQDs in conjunction with garlic extract as a green chelating agent to maintain its enhanced sensitivity was successfully applied with good recoveries ranging from 89.16 to 121.45%.
Keywords: Carbon and Quantum Dots Applications